Acceptance and the influencing factors towards intermittent self-catheterisation among patients with neurogenic lower urinary tract dysfunction in China: a multicentre cross-sectional study - Wenzhi Cai; Dan Wu; Ling Chen; YingJie Hu; Fengming Hao; Senying Luo; Laifu Wang (BMJ Open)
Objectives The psychological acceptance of intermittent self-catheterisation (ISC) significantly impacts its initial adoption and long-term compliance among patients. However, our understanding of this acceptance remains limited. This study aims to investigate ISC’s psychological acceptance and identify influencing factors among neurogenic lower urinary tract dysfunction (NLUTD) patients in China.Design A cross-sectional study design.Participants A total of 394 patients with NLUTD were recruited from 15 tertiary general hospitals in China.Outcome measure The patients completed a comprehensive questionnaire that included demographic and clinical characteristics, along with study instruments such as the Intermittent Catheterization Acceptance Test (I-CAT), the Intermittent Catheterization Satisfaction Questionnaire (InCaSaQ), the Intermittent Catheterization Difficulty Questionnaire and the Intermittent Self-Catheterization Questionnaire (ISC-Q). Pearson’s correlation analysis explored interrelationships among questionnaire scores, while Spearman’s correlation assessed relationships between categorical independent variables and I-CAT scores. Additionally, multiple linear regression analysis identified key factors influencing psychological acceptance of ISC.Results Nearly half of the participants (46.2%) reported psychological challenges in accepting ISC, and more than 50% of the participants exhibited fear and low self-esteem in their I-CAT questionnaire scores. The I-CAT scores were strongly correlated with ISC training (r=0.861), ISC follow-up (r=0.766) and psychological well-being (r=−0.774). Regression analysis identified significant factors influencing ISC acceptance, including urinary tract infections, types of catheters, ISC training, ISC follow-up, province, and scores on the ISC-Q and InCaSaQ questionnaires, which collectively explained 85.5% of the variance in acceptance rates (F=161.409).Conclusions Psychological difficulties in accepting ISC are prevalent among NLUTD patients. Key factors that facilitate ISC acceptance include receiving ISC training, follow-up support and favourable ISC-Q scores. In contrast, barriers like the use of non-hydrophilic catheters present significant challenges. Notably, ISC acceptance varies significantly across different regions. Therefore, targeted strategies are recommended to enhance positive factors, reduce negative ones and consider regional disparities, thereby improving overall ISC acceptance.